2019
DOI: 10.1177/1071100719853291
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Subtalar Fusion and Calcaneal Osteotomy on Function, Pain, and Gait Mechanics for Calcaneal Malunion

Abstract: Background: Calcaneal malunion is a common complication of nonoperative management of calcaneal fracture, which leads to a disruption of the biomechanics of the lower extremity, pain, and permanent disability. Our aim was to evaluate pain, function, and gait after combined subtalar joint fusion, calcaneal osteotomy, and lateral wall exostectomy for patients with neglected calcaneal fractures with malunion. Methods: Eighteen patients with malunited calcaneal fractures, varus deformity, and subtalar arthritis we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Adjustment of the hindfoot alignment in a slight valgus position could lessen the pressure on the lateral column. 26,31 Farouk et al 16 presented that in cases with malunion, valgus calcaneus osteotomy combined with subtalar fusion could lead to improvement in the gait of patients. In our study, a moderate shift of the loading from the medial to the lateral column was seen, showing statistically significant increase of pressure distribution only on the lateral forefoot (lateral forefoot P = .018).…”
Section: Discussionmentioning
confidence: 99%
“…Adjustment of the hindfoot alignment in a slight valgus position could lessen the pressure on the lateral column. 26,31 Farouk et al 16 presented that in cases with malunion, valgus calcaneus osteotomy combined with subtalar fusion could lead to improvement in the gait of patients. In our study, a moderate shift of the loading from the medial to the lateral column was seen, showing statistically significant increase of pressure distribution only on the lateral forefoot (lateral forefoot P = .018).…”
Section: Discussionmentioning
confidence: 99%
“…Lateral stability requires active adjustment. And longitudinal stability passive adjustment through the conversion of energy absorbed by the stride and loading response to gradually eliminate external disturbances reduces the impact [ 4 ]. In contrast to previous research, this study carried out a correlation analysis of the dynamic indicators in the stance phase as well as an analysis of the differences between the groups according to gait events.…”
Section: Discussionmentioning
confidence: 99%
“…The frequently occurring traffic accidents, cardiovascular and cerebrovascular events, and the increasing aging of the population in our society have led to the presence of large numbers of potentially or apparently unstable gait holders. Moreover, in the available studies, cases of decreased gait stability or abnormal gait due to disease [1][2][3] and surgery [4,5] have been reported. Falls and their secondary injuries caused by instability of gait often have serious consequences.…”
Section: Introductionmentioning
confidence: 99%
“…The restoration of anatomy can help improve gait and prevent complications such as calcaneofibular impingement, subfibular impingement, decreased tibiotalar motion, and calcaneal widening, resulting in poor shoe wear. 2,20,22,36,41,43,47 Radnay et al 41 reviewed patients who underwent delayed STA, stratifying them by initial treatment as either nonoperative or ORIF. Their results showed that patients initially treated nonoperatively who then underwent a subtalar arthrodesis for painful malunion had worse functional outcomes and higher complications than patients managed with initial ORIF.…”
Section: Discussionmentioning
confidence: 99%